The war over America’s Health Care: an application of the advocacy coalition framework to the Affordable Care Act - Mofulatsi, Mofenyi Kgotso (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.